Perencanaan Dan Pelaksanaan Program Dakwah SMP Annur Prima Dalam Peningkatan Kemampuan Baca Al Quran Siswa - Alfariz, M. Raihan; Abdullah, Abdullah (Universitas Cokroaminoto Yogyakarta, 2025)
The purpose of the qualitative study was to determine the planning and implementation of the da'wah program in improving the ability to read the Qur'an of Annur Prima Junior High School students, the factors in improving the ability to read the Qur'an, as well as its effectiveness, and solutions that can be applied. Data collection techniques through interviews, observations, and documentation. The results showed that The planning of the da'wah program carried out by improving the ability to read the Qur'an, making the young generation rahmatan lilalamin, understanding Tahsin and tahfizd Qur'an, reading and writing verses of the Qur'an. The implementation of the da'wah program of Annur Prima Junior High School, Talaqqi Al Qur'an, Tilawah Al Qur'an, Tahfidz Al Qur'an, and Tartil Al Qur'an. In terms of effectiveness, the major challenges are the lack of support from parents of students, as well as the social environment, and the current development of social media.